Studies on Stress Corrosion Cracking of Vit 105 Bulk Metallic Glass - Gebert, Annett; Geissler, David; Pilz, Stefan; Uhlemann, Margitta; Davani, Farnaz A.; Hilke, Sven; Rösner, Harald; Wilde, Gerhard (Frontiers in Materials, 2020)
The project “Stress Corrosion Cracking of Zr-based Bulk Metallic Glasses” (SCC of Zr-BMG) within PP1594 mainly dealt with mechanical-corrosive interactions and failure of this class of metastable materials. It focussed on one of the most application-relevant Zr-BMG, Vit(reloy) 105 with composition Zr52.5Cu17.9Ni14.6Al10Ti5 (at.-%). Even though this BMG is known as extraordinary glass former, the metallurgical processing is still a critical issue. In contrast to conventional processing, i.e. melting of master alloys from pure elements, a different route using binary pre-alloys for the master alloys production was applied and led to superior mechanical properties upon mechanical testing under tensile and 3-point-bending (3PB) conditions in air. As a reference and for a detailed understanding of failure, fracture and cracking of Zr-base BMG in air, notched specimen 3PB experiments with in-situ microscopic observation were done and the still controversial interpretation of the mechanical behaviour of BMG in the framework of fracture mechanics was addressed. The specimen from the in-situ 3PB-tests served for TEM investigations on the structural nature of shear bands in BMG on the atomistic scale. Altogether, complete crack paths could be observed and analysed and based on this, details of the shear-band driven crack growth are described. While in first SCC studies using a newly developed setup full cross section (3PB) bars were investigated, in recent in situ experiments notched specimen were tested in 0.01 M NaCl yielding strong evidence for a catastrophic failure due to hydrogen embrittlement (HE). The known susceptibility to pitting corrosion in halide containing environments is only the initial stage for failure under SCC conditions. Once pitting is initiated, the local electrode potential is severely reduced. Further, the hydrolysis reaction of oxidised Zr4+ to zirconyl ions ZrO2+ during local BMG dissolution produces H+ and thus, a local acidic environment that enables proton reduction and hydrogen absorption in the stressed BMG region. The peculiar failure and fracture surface characteristics as well as the proven local reduction of the pH value in the vicinity of the notch during in-situ experiments clearly account for the proposed HE-SCC failure mechanism.